Computer Solutions of Management for the Development Process of New Products. (2015) - Alexe, Cătălin-George; Alexe, Cătălina-Monica
Abstract: The success in new product development (NPD) is based on understanding and correctly anticipating the market needs by identifying opportunities taking into consideration the company's potential and knowledge. Thus, the company's management is facing serious challenges, with regular character on the allocation of organizational resources to launch the product at the right time. The questions that arise are how much big companies in the industry have evolved by providing information solutions of management that are considering the running through several steps in the development of new products, as well as mentioning those punctual solutions on certain stages proposed by smaller firms in the industry. The paper is proposing that starting from a model of the product development process, own conception, based on the study of several other models in the literature, to identify various current information solutions via the Internet useful in going over the steps of the product lifecycle management (PLM). At the same time, with the identification will be achieved a comparative analysis of these solutions in order to see the complexity of the solution and the possibility of its application.